Preservation of Megalithic Sites as Integrated Tourism Objects in Lahat Regency, South Sumatra (Paramita: Historical Studies Journal, 2020)
Megalithic sites, tourist assets in Lahat Regency besides waterfalls, are a wealth of culture in the past that have the potential to be a tourist attraction. The location of megalithic sites scattered in several subdistricts and mostly located outside the settlement becomes an obstacle to be developed as a tourist destination. The purpose of this research is to develop an integrated tourism strategy that composes megalithic sites, natural attractions, artificial attractions, settlements, and the empowerment of local communities. This research combines historical research and case study. The case study is used by observing the location of megalithic sites in several districts in the Lahat Regency. The rapid mapping of potential megalithic sites and tourist objects and developed into two zonings. Community empowerment is conducted by focusing on group discussion (FGD) involving related parties. Megalithic sites are unique, scattered over a wide area, and different geographic conditions make them difficult for tourists to visit. There are several megalithic sites in the settlement, plantation, or rice fields. Local Communities already have an understanding of utilizing homes as homestays. It is concluded that the determination of zonation in Lahat regency can direct the management of the megalithic site as a tourism object according to the site characteristics and the built environment through community empowerment. The first zoning is the location of megalithic sites on Pagaralam as the direction of tourist arrivals with the village of Gunung Kaya in the Jarai sub-district as the node, and the second zonation on Lahat as the direction of tourist arrivals with the village Sinjar Bulan in Gumay Ulu sub-district as the node. Megalithic site management strategy as an integrated tourist attraction is also carried out by utilizing all the existing potential.Situs megalitik adalah warisan budaya di masa lalu yang berpotensi menjadi objek wisata. Lokasi situs megalitik yang tersebar di beberapa kecamatan dan sebagian besar berada di luar pemukiman menjadi kendala untuk dikembangkan sebagai tujuan wisata. Tujuan dari penelitian ini adalah untuk mengembangkan strategi pariwisata terpadu yang menyusun situs megalitik, atraksi alam, atraksi buatan, permukiman, dan pemberdayaan masyarakat lokal. Penelitian menggunakan dua pendekatan, yakni penelitian historis dan studi kasus. Situs megalitik unik, tersebar di wilayah yang luas, dan kondisi geografis yang berbeda membuat mereka sulit dikunjungi wisatawan. Ada beberapa situs megalitik di pemukiman, perkebunan, atau sawah. Masyarakat setempat sudah memiliki pemahaman tentang pemanfaatan rumah sebagai homestay. Disimpulkan bahwa penentuan zonasi di Kabupaten Lahat dapat mengarahkan pengelolaan situs megalitik sebagai objek wisata sesuai dengan karakteristik situs dan lingkungan binaan melalui pemberdayaan masyarakat. Zonasi pertama adalah lokasi situs megalitik di Pagaralam sebagai arah kedatangan wisatawan dengan desa Gunung Kaya di kecamatan Jarai sebagai simpul, dan zonasi kedua di Lahat sebagai arah kedatangan wisatawan dengan desa Sinjar Bulan di kecamatan Gumay Ulu sebagai simpul.